The prevalence and factors associated with malnutrition among infants with cleft palate and/or lip at a hospital in Uganda: a cross-sectional study - Tungotyo, Martin; Atwine, Daniel; Nanjebe, Deborah; Hodges, Andrew; Situma, Martin (BMC pediatrics, 2017)
Background: To determine the prevalence and factors associated with malnutrition among infants with Cleft palate and/or cleft lip (CP+/-L) at Comprehensive Rehabilitation for Uganda Hospital (CoRSU) in Uganda. Methods: This was a cross-sectional study done on infants with CP+/-L and their caretakers admitted between November 2013 and October 2014 at CoRSU hospital which was the study setting. A questionnaire was answered by the infants’ caretakers. The main outcome measure, malnutrition was defined and classified based on Z-scores obtained using the W.H.O Z calculator in which weights of the infants in kilograms and lengths in centimeters respectively were placed. The values obtained were expressed as a proportion using all enrolled infants with CP+/-L as denominator. Multivariable analysis was used to determine the risk factors. Results: A total of 44 infants with CP+/-L were enrolled. Of these, 77% were below 4 months of age and 97.7% were immunized. The male-to-female ratio was 1.06:1. About 59% had unilateral CP+/-L. A total of 93.2% were delivered at term with 69.4% having a birth weight greater than 3 kg. Generally, 68% were malnourished, with the highest burden among females (71.4%), infants below 4 months (73.5%) and those with unilateral CP+/-L (77%). About 57% had moderate-to severe malnutrition. There was delayed supplementation to breast milk, with cow-milk as the main supplemental feed for all the infants. In the multivariable analysis, factors associated with malnutrition included, having caretakers lacking nutritional information post-delivery (OR = 3.8, p = 0.17), low birth weight (OR = 3.4, p = 0.20), and having less than 10 feeds/day (OR = 4.9, p = 0.09). Conclusion: CP+/-L infants born in Uganda suffer a high-burden of malnutrition. Preventional strategies are needed with focus on proper feeding information. Research on cost-effective feeds, feeding methods and reasons behind gender disparities in these infants is also required
Keywords: Cleft palate; Infant; Malnutrition